Examining the Potential Synergistic Effects Between Mindfulness Training and Psychedelic-Assisted Therapy - Eleftheriou, Maria Eleni; Thomas, Emily (Frontiers in Psychiatry, 2021)
Mindfulness-based interventions and psychedelic-assisted therapy have been utilised in recent years as alternative treatments for various psychopathologies with moderate to great success. Both have also demonstrated significant post-acute and long-term decreases in clinical symptoms and enhancements in well-being in healthy participants. These two therapeutic interventions share various postulated salutogenic mechanisms, such as the ability to induce life-changing mystical experiences and corresponding neuromodulatory effects, as well as anti-depressive action. Recent preliminary evidence has also demonstrated that psychedelic administration can enhance mindfulness capacities which has already been demonstrated robustly as a result of mindfulness-based interventions. These shared mechanisms between mindfulness-based interventions and psychedelic therapy have led to scientists theorising, and recently demonstrating, synergistic effects when both are used in combination. These synergistic results hold great promise but require replication in bigger sample groups and better controlled methodologies, to fully delineate the effect of set and setting, before they can be extended onto clinical populations.